Unpacking the connections between 8th graders' climate literacy and epistemic cognition. Issue 10 (22nd June 2021) - Quarderer, Nathan Anderson; Fulmer, Gavin W.; Hand, Brian; Neal, Ted A.
Abstract: Our epistemic cognition informs what scientific claims we choose to endorse over others, how we come to know in science, and our assumptions about the construction of scientific knowledge. The topic of climate change provides context for how we come to know about our surrounding environment. The development of climate literacy in young learners has received heightened attention over the last decade. What learners choose to believe about the topic of climate change presents an epistemic challenge for science educators as they help students navigate through a sea of information that often contains competing claims. The study described here examines how climate literacy and epistemic cognition interact in a group of 8th grade students in the Midwestern United States. Findings from Rasch analysis of survey responses and coding of student interviews suggests a positive relationship between learners' climate literacy and epistemic cognition, with participants tending to exhibit quasi‐reflective judgment when justifying their beliefs about the causes and effects of climate change, how scientists come to know about Earth's climate, and the level of certainty that researchers have about changes to our climate system. Implications for the development of learning environments that help shape adolescents' epistemic cognition and engage with the topic of climate change using place‐based learning and teaching materials will be discussed.